Dynamic externalities and regional manufacturing development: An exploration of the Polish experience before and after 1989 - Roger Bivand; Jon M. Steineke (European Regional Science Association (ERSA), 1998)
The impact of localization and urbanization economies on regional manufacturing development in Poland 1976-96 is assessed in terms of employment and the regional convergence or divergence of the economy. We examine current research on the role of dynamic production externalities in regional manufacturing development, starting with a review of recent literature on the nature of such externalities in manufacturing location, and how positive externalities may influence the spatial clustering of manufacturing industries. While much of the current literature is focussed on US experience, we analyse manufacturing employment data for Poland, in order to explore to what extent conclusions drawn from US experience may illuminate a regional economy in transition. The analysis also pays attention to the integration of a number of different methods from differing traditions, from economic geography, regional science, and new economic geography, including location quotients, Gini indices, shift-share, analysis of variance, Poisson regression, and Poisson regression for panel data. We find that radical changes have occurred in patterns of Polish regional manufacturing employment, both with regard to sectors and regions. Transition is refocussing the regional economy on strong regional centres, and on sectors regarded with little favour in the planned economy, such as food processing and wood products, including furniture.
Keywords: 330